The Service Quality of Population Document to Improve Community Satisfaction Index - Taan, Hapsawati (AIBPM Publisher, 2020)
The research aims at 1) perceiving the service quality of population document 2) discovering problems in improving the quality of public service 3) understanding the attempts conducted by The Office of Population Affairs and Civil Registration in Gorontalo City to cope with the problems in the quality of public service. The research uses a qualitative approach with an in-depth interview, observation, and documentation technique. The informant is the head office and the customer service of the object being observed. The techniques of data analysis are data reduction, data display, and conclusion. The research result indicates that The Office of Population Affairs and Civil Registration in Gorontalo City has not fulfilled the public service facility maximally such as facilities and infrastructures, and human resources. Meanwhile, the staff has shown their best to respond and help the community when they have problems in processing population documents. It concludes that the quality of public services in the office can be observed from five dimensions such as tangibles, reliability, responsiveness, assurance, and empathy.